KAMPUNG KECIL DENGAN ISU BESAR: Deskripsi kondisi Sosial Ekonomi dan Pendidikan Masyarakat Desa Bangga Kec. Paguyaman Pantai Kab. Boalemo Tahun 2010-2011 - Helman Manay (Jambura History and Culture Journal, 2021)
This long article is a summary of the results of field research conducted by the author in 2011 in Bangga Village, Kec. Paguyaman Beach District. Boalemo, Gorontalo Province for the support from the SUSCLAM Program. Bangga is a village which until now has become a center for producing rowa smoked fish, the main ingredient for making rowa sauce which is famous in the northern region of Sulawesi. Even though it is abundant with marine products, its isolated geographical position due to poor road infrastructure means that the local community's economic condition has not moved beyond the poverty line. This has an impact on access to higher education which is also low. This condition prompted the Tomini Bay program (SUSCLAM/Sustainable Coastal Livelihood and Management) to choose Desa Bangga as one of the locations for the implementation of the program funded by the Canadian government. The Tomini Bay program intervention for 5 years (2008-2013) had a significant impact on the economic development and ecological awareness of the local village community. This article discusses two important aspects of the life of the Bangga community, namely socio-economic and education. Even though it only covers a short period (2010-2011), this research is expected to be a comparison of research on coastal communities, especially in Tomini Bay after that period.